Valoracion de los saberes ancestrales para la conservación del patrimonio cultural inmaterial en la parroquia San Luis Canton Riobamba Provincia de Chimborazo. - Cujilema Pucar, Jesica Alejandra (2016)
The ancestral knowledge is a set of knowledge that our ancestors acquired empirically over time and circumstances which were useful to benefit from the resources without affecting other elements or individuals, promoting the solidarity and respect between they and the nature or Pacha Mama, the knowledge was transmitted by generations. While the technology advances by leaps and bounds and the actual generation adopts it like majority axis of its life leaving aside the culture, this one generates a problem because to there is no a balance between the use of the resources and its preservation, exceeding the limitations of the Pacha – Mama has so that there is “Buen Vivir” . Ecuador is considered a multi-diverse country thanks to different nationalities that preserve its culture, the transformation of the technologies not advanced in an entire or maximum percentage for it according to the established in the “Buen vivir” through the constitutional frame of the science, the technology and the ancestral knowledge, it has like purposes; to recover, to strengthen and to promote the ancestral knowledge to maintain, to protect and to develop the collective knowledge; its sciences, technologies and ancestral knowledge. The present research takes as an object to identify the value of the ancestral knowledge found in the investigation by means of an analysis of the current situation of the knowledge by means of skills of investigation, the observation, field work, interviews, surveys and the making of a record of knowledge to promote the conservation before these get lost partially or completely. The steps to be continued in the investigation were divided in the following chapters; the first chapter will contain the theoretical foundation, in the second chapter there will be established the methodology to be used, the fourth chapter will analyze the results that it projects according to the used methodologies, the chapter five and six will contain a discussion of the results.